Audit of the quality and cost of acute inpatient stroke care in the general medical wards at Groote Schuur Hospital - Viljoen, Charle André (Department of Medicine, 2016)
Introduction: Stroke is the leading cause of death and disability amongst South Africans older than 60 years. The majority of stroke patients in South Africa are managed in general medical wards where little is known about the quality and cost of care. The aim of this study was to determine the cost of stroke care and to identify factors associated with increased expense , as well as to evaluate the quality of stroke care in general medical wards in order to identify areas where quality of care could be improved. Methods: We conducted a retrospective folder review of all acute stroke admissions to the general medical wards at Groote Schuur Hospital from 1 January to 31 December 2012. Patients younger than 45 years and those that received thrombolysis were excluded. The hospital's finance department provided the bed costs, as well as expenditure on consumables, pharmacy, laboratory and radiology for each subject. The quality of care was measured according to the South African Stroke Guidelines. Results: The inpatient care of 261 patients was evaluated. Although neuroradiology was performed on 95% of patients, carotid duplex Doppler ultrasonography and echocardiography were not often done. Although all patients with ischaemic stroke received inpatient antiplatelet or anti - coagulation therapy, not all risk factors were adequately addressed on discharge. The median cost of a stroke admission was R19,072.07 (IQR R10,899.85 to R27,789.43 ). The strongest correlation with cost 12 was with length of stay (LOS), r = 0.9977. The median LOS was 6 days (IQR 3 to 9 days). Using non -¬‐ parametric univariable analysis, clinical factors prolonging LOS were previous stroke ( P = 0.0 2 8) and inpatient complications: fever ( P < 0.0 0 1), urinary tract infections ( P < 0.0 0 1) and acute kidney injury ( P < 0.0 0 1) . The LOS increased as the number of inpatient complications increased (P = 0.059). Mortality was 20% and 68% of patients experienced at least one medical complication during admission. Fever and pneumonia were predict ors of death. Pneumonia was less prevalent amongst patients who were mobilised early (P = 0.002). Early nutritional support was beneficial in reducing the incidence of acute kidney injury (P < 0.001). The median LOS was significantly prolonged by delaying speech therapy (P < 0.001), nutritional support (P < 0.01), physiotherapy (P < 0.01) and occupational therapy (P < 0.001). Discharge to inpatient rehabilitation centres significantly prolonged LOS as compared with patients discharged home (P < 0.001). Conclusions: This is the first study evaluating the cost of acute stroke care in South Africa. Length of stay was the greatest determinant of cost. Improving the quality of care to reduce the number of complications, early referral to allied health professionals and effective discharge planning would result in shorter length of hospital stay and therefore cost saving. There is a need for increased access to stroke unit beds, albeit dedicated stroke beds in the general medical wards, to ensure specialised nursing care and early inpatient rehabilitation to reduce the number of inpatient complications, as well as implementation of protocols to allow for better adherence to national guidelines.